2015
DOI: 10.1007/s00300-015-1706-z
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the deep-sea tanaidacean fauna of the Ross Sea: species richness and composition across the shelf break, slope and abyss

Abstract: Tanaidaceans belong to the most severely underestimated groups of benthic macrofauna of the Southern Ocean. Here, we analyze 11 samples collected with a small-meshed epibenthic sled in the summer season of 2008, in the Ross Sea, at the shelf break, slope and abyss (365-3490 m). The material was obtained during a RV Tangaroa voyage as part of the New Zealand International Polar Year, Census of Antarctic Marine Life Project. Seventy-two species of Tanaidacea were recorded, 85 % of which were new to science. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…Brandt et al (2009) analysed the bathymetric depth ranges at polychaete family level within 100 m depth bins, showing that most families were spread over several thousand meters, although, species-level data may be more appropriate to assess depth zonation. Kaiser et al (2011) showed that many isopods in the Southern Ocean were restricted to slope depths with a possibility of the existence of a unique Southern Ocean slope fauna, Recently, tanaid data from the Ross Sea suggested the presence of a distinct slope fauna and strong structuring of tanaid assemblages by depth (Pabis et al 2015b). The use of DNA techniques for taxonomic purposes has revealed the existence of cryptic species in Southern Ocean fauna (e.g.…”
Section: Discussion Large-scale Patterns In Polychaete Assemblagesmentioning
confidence: 99%
“…Brandt et al (2009) analysed the bathymetric depth ranges at polychaete family level within 100 m depth bins, showing that most families were spread over several thousand meters, although, species-level data may be more appropriate to assess depth zonation. Kaiser et al (2011) showed that many isopods in the Southern Ocean were restricted to slope depths with a possibility of the existence of a unique Southern Ocean slope fauna, Recently, tanaid data from the Ross Sea suggested the presence of a distinct slope fauna and strong structuring of tanaid assemblages by depth (Pabis et al 2015b). The use of DNA techniques for taxonomic purposes has revealed the existence of cryptic species in Southern Ocean fauna (e.g.…”
Section: Discussion Large-scale Patterns In Polychaete Assemblagesmentioning
confidence: 99%
“…Pseudotanaidae (Sieg 1976) species represent a frequent and diverse element of deep-sea benthic assemblages, only exceeded by polychaetes 28,29 . The genus Pseudotanais is the most speciose within the family, formed by four species-groups: ‘affinis’, ‘denticulatus’, ‘forcipatus’ and ‘longisetosus’, based on morphological variation in key traits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The IceAGE cruises carried out in 2011 and 2013 (Brix et al 2013) provided an opportunity to obtain a large collection of tanaidaceans and the family Pseudotanaidae Sieg, 1976 accounted for a substantial part of it (unpublished data of the authors). The family is widespread in the world's ocean, and its members being encountered within a wide depth range: from 0.5 to over 7000 m (Bird and Holdich 1989a;Błażewicz-Paszkowycz et al, 2012;Pabis et al 2015). Pseudotanaids have been reported from different habitats, e.g., hard bottom, algae, coral reefs, cold seeps, mud volcanos, and hydrothermal vents (Bird 1999;Błażewicz-Paszkowycz and Bamber 2011;Larsen, 2012;Stępień unpublished data).…”
Section: Introductionmentioning
confidence: 99%